Correlation of mother's educational background with autistic children's independence - Yeanny Suryadi (Institute of Computer Science (IOCS), 2023)
The prevalence of autism, which continues to increase, creates anxiety for autistic parents in particular and for the environment in general about their self-reliance in adults. Institutions of special needs schools are moving swiftly to create an adaptive autistic potential and an independent human being. This research proves, there's no relation above of mother's education and their children's self-reliance, when they were studying at school or even when there were staying at home. Saturated total sampling for this research are 20 students from special needs schools in Deli Serdang. The result of data processing is using the SPSS application and Excel application, with the value achieved is 0.097, meaning there's no relation above mother' education and their self-reliance.